If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 150 = x(60) Reorder the terms for easier multiplication: 150 = 60x Solving 150 = 60x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-60x' to each side of the equation. 150 + -60x = 60x + -60x Combine like terms: 60x + -60x = 0 150 + -60x = 0 Add '-150' to each side of the equation. 150 + -150 + -60x = 0 + -150 Combine like terms: 150 + -150 = 0 0 + -60x = 0 + -150 -60x = 0 + -150 Combine like terms: 0 + -150 = -150 -60x = -150 Divide each side by '-60'. x = 2.5 Simplifying x = 2.5
| 5x-22+(4x+4)=90 | | .75a=14.25 | | 50x^2=450 | | 3.2x-0.88+1.2x=0 | | x+y+24=32 | | -4=-28+n | | -20+50y=100 | | (6x-10)+6x+10=180 | | -3-5(5x+7)=0 | | a-0.01a=33 | | -3(-6r-6)-5(7+7r)=-51 | | 3.4=-1.7y | | y-44=38(23+x)+21 | | 9x^2-7=-151 | | 0.75h+4=7 | | -12x+4y=28 | | 70+4x-2y=180 | | 10.1x=0.2(x+2) | | 5c+10=c-10 | | 0.75+4=7 | | 4.3y=47.3 | | 85(t)=-16x^2+85 | | 2b+3z=x(2b+3z) | | 5c+9=c-3 | | X-64=-6x+62 | | 6x+4x-2=16 | | 44=-4(1+6b)-6(-5b-1) | | 59+11p=-29 | | 3(5e-3)=e+4 | | 6a+a=84 | | 30(6)+5y=90 | | X-43=-4x+27 |